Desenvolvimento e validação de método para quantificação da capacidade redutora de extratos vegetais e secos - Novaes, Jussival de Abreu Pinheiro (2008)
The developed method in this work is defined as a chemical method of indirect quantification of the reducing capacity of vegetable extracts. It is based on the reduction of ions Fe3+ by chemical substances contained in the extracts and subsequent quantification of Fe2+ ions for spectrophotometric technique in range of the visible using the adapted method of the reagent 1,10-phenanthroline. The procedure of the development and validation was composed by three parts: characterization of the quantification of Fe2+ in the form of the complex [Fe(fen)3]2+; reduction of ions Fe3+ by organic compounds and vegetable extracts; and characterization of the proposed method. Ascorbic acid, hydroquinone, catechol, pirogallol, quercetine, Trolox™, BHA, BHT, cisteine and glutathione were used as reference reducing. The samples of dry vegetable extract were obtained from bank of extracts of the Laboratory of Bioprospection and Biotechnology, installed in the Coordenação de Pesquisas de Produtos Naturais (CPPN) of the Instituto Nacional de Pesquisas da Amazônia (INPA). The criterion for the choice of the extracts used in the validation process was based on measures (peaks or oxidation bands) by cyclic voltammetry technique. The compound [Fe(fen)3]2+ is stable and in the tested conditions it did present maximum absorption in 508.8 nm with molar absorptivity around (1.084 ± 0.003) × 104 L.mol-1.cm-1. The quantification of ions Fe2+ in the form of the compound [Fe(fen)3)]2+ is linear in the range from 0.2 to 10.0 g.mL-1. The adjusted line obtained by the method of minimum squares presented equation ABS = 0.01444 ± 0.19417 × [Fe2+] (R2 = 0.9994) for concentrations up to 10.0 g.mL-1 and ABS = 0.00263 ± 0.19974 × [Fe2+] (R2 = 0.9997) up to 5.5 g.mL-1. Established oxidation process consists of two stages: (1) reaction with ions Fe3+ and (2) reaction with ions Fe3+ in the presence of 1,10-phenanthroline. The oxidation degree and the linearity vary in agreement with the reaction mechanism. The proposed method presented positive answer for the glutathione, differently of other methods described in the literature. The developed method and validated presents the following characteristics: Limit of decision, of detection and of quantification was of 0.17 g Fe2+.mL-1 , 0.20 g Fe2+.mL-1 and 0.31 g Fe2+.mL-1, respectively; Reproducibility and repeatability between 0.5% and 3.9%; absolute discrepancy between 1.3% and 3.9% for the following reducing: ascorbic acid, hydroquinone and BHA. Ethanol, methanol, acetone and DMSO can be used to dissolve the vegetable extracts. Ethylene glycol and DMF can be used, but they can coordinate with Fe2+/Fe3+ ions. The coordination of the Fe2+/Fe3+ ions for ligands present in the extract are labile in relation to chelante 1,10-phenanthroline. The Co2+, Cu2+, Ni2+, Mn2+, Sn2+, Zn2+, Mg2+, Ca2+, Na+, K+, NH4+, SO42-, Cl- e NO3don't interfere in the quantification of the complex [Fe(fen)3]2+, but PO43- ion interfere in higher concentrations than 10 g Fe2+.mL-1. The UV radiation produces false positive, converting Fe3+ in Fe2+. With base in the obtained results, it can be concluded that the method developed for quantification of the reducing capacity of vegetable extracts was appropriate and of easy execution.